Identification of a transcriptional enhancer important for enteroendocrine and pancreatic islet cell-specific expression of the secretin gene. - Wheeler, M B (1992)
It is well established that the gene encoding the hormone secretin is expressed in a specific enteroendocrine cell, the S cell. We now show that the secretin gene is transiently expressed in insulin-producing B cells of the developing pancreatic islets in addition to the intestine. Furthermore, secretin is produced by most established islet cell lines. In order to identify and characterize the regulatory elements within the secretin gene that control tissue-specific expression, we have introduced secretin reporter gene constructions into the secretin-producing HIT and STC-1 cell lines as well as the nonexpressing INR1-G9 glucagonoma line. Analysis of deletion mutants revealed that sequences between 174 and 53 bp upstream from the transcriptional start site are required for maximal expression in secretin-producing cells. This positive element functioned independently of position and orientation. Further deletions into the enhancer resulted in a stepwise loss of transcriptional activity, suggesting the presence of several discrete control elements. The sequence CAGCTG within the secretin enhancer closely resembles that of the core of the B-cell-specific enhancer in the insulin gene. Point mutations introduced into this putative element led to greater than 85% reduction in transcriptional activity. Gel mobility shift assays suggested that a factor in B cells closely related or identical to proteins that bind to the insulin enhancer interacts with the CAGCTG motif in the secretin gene.